Oceanic forcing of penultimate deglacial and last interglacial sea-level rise - Clark, Peter U.; He, Feng; Golledge, Nicholas R.; Mitrovica, Jerry X.; Dutton, Andrea; Hoffman, Jeremy S.; Dendy, Sarah (Nature (London), 2020)
Sea-level histories during the two most recent deglacial–interglacial intervals show substantial differences 1 – 3 despite both periods undergoing similar changes in global mean temperature 4 , 5 and forcing from greenhouse gases 6 . Although the last interglaciation (LIG) experienced stronger boreal summer insolation forcing than the present interglaciation 7 , understanding why LIG global mean sea level may have been six to nine metres higher than today has proven particularly challenging 2 . Extensive areas of polar ice sheets were grounded below sea level during both glacial and interglacial periods, with grounding lines and fringing ice shelves extending onto continental shelves 8 . This suggests that oceanic forcing by subsurface warming may also have contributed to ice-sheet loss 9 – 12 analogous to ongoing changes in the Antarctic 13 , 14 and Greenland 15 ice sheets. Such forcing would have been especially effective during glacial periods, when the Atlantic Meridional Overturning Circulation (AMOC) experienced large variations on millennial timescales 16 , with a reduction of the AMOC causing subsurface warming throughout much of the Atlantic basin 9 , 12 , 17 . Here we show that greater subsurface warming induced by the longer period of reduced AMOC during the penultimate deglaciation can explain the more-rapid sea-level rise compared with the last deglaciation. This greater forcing also contributed to excess loss from the Greenland and Antarctic ice sheets during the LIG, causing global mean sea level to rise at least four metres above modern levels. When accounting for the combined influences of penultimate and LIG deglaciation on glacial isostatic adjustment, this excess loss of polar ice during the LIG can explain much of the relative sea level recorded by fossil coral reefs and speleothems at intermediate- and far-field sites. A reduction in the strength of the Atlantic Meridional Overturning Circulation initiated during the penultimate deglaciation led to excess polar ice losses, contributing to higher sea levels during the last interglacial period.